The Effect of Debt Policy, Independent Commissioners, and Firm Size on Firm Value - Dea Sinta Mirela; Galuh Tresna Murti; Muhamad Muslih (Green Publisher Indonesia, 2025)
Company value describes the success of a company as reflected by a company's share price. The purpose of this study is to determine the influence of debt policy, independent commissioners, and company size on the value of the company. The object of this research is a food and beverage subsector company listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sample was selected using a purposive sampling technique with certain criteria so that a sample of 45 companies was obtained. The analysis used in this study was a regression analysis of panel data using the Eviews 12 ghost tool. The results of this study show that debt policies, independent commissioners, and company size simultaneously affect the value of the company. Partially, the debt policy has a positive effect on the company's value. Meanwhile, independent commissioners and company size have no effect on the company's value.